Comparison of the VO2 Master Pro and Cosmed K5 during walking, jogging, and running - Toulouse, A.; Joubert, D.; Oden, G.; Davis, P. R. (Journal of Science in Sport and Exercise, 2022)
Aim: Portable devices that accurately detect the composition of expired gases and changes in VO2 open new possibilities in research methodology and accessibility. Purpose: The purpose of this study was to compare the oxygen consumption (VO2) measurements of the VO2 Master Pro (VM) to the Cosmed K5 (K5) during walking, jogging, and running in field and lab conditions. Methods: Twelve proficient runners, with a current 10 k pace of = 11.29 km/h, performed 3 matched intervals at 3 different speeds (4.82, 8.05, 11.29 km/h) on a treadmill and on an outdoor track. An airflow test was also performed on both devices by pumping air through the devices using a 3 L syringe timed to a metronome at 15, 25, and 35 beats/min. Results: The VM did not report walking data for most participants. During treadmill running, there were significant differences in VO2 (47.86 ± 3.94 vs. 29.56 ± 4.15 mL/kg/min), ventilation (Ve) (71 vs. 57 mL/min), and tidal volume (TV) (1.89 vs. 1.56 L) between the K5 and VM respectively (P < 0.05). Outdoor analysis also showed significant differences between devices in VO2, Ve, and TV (P < 0.05). The airflow test showed significant differences between the devices in Ve and TV (P < 0.05). Conclusion: These results suggest that there are significant discrepancies between the K5 and the VM, likely due to differences in TV measurement.